Imaging of Titan from the Cassini spacecraft - Porco, C.; Baker, E.; Barbara, J.; Beurle, K.; Brahic, A.; Burns, J.A.; Charnoz, S.; Cooper, N.; Dawson, D.D.; Del Genio, A.; Denk, T.; Dones, L.; et al. (Nature, 2005)
Titan, the largest moon of Saturn, is the only satellite in the Solar System with a substantial atmosphere. The atmosphere is poorly understood and obscures the surface, leading to intense speculation about Titan's nature. Here we present observations of Titan from the imaging science experiment onboard the Cassini spacecraft that address some of these issues. The images reveal intricate surface albedo features that suggest aeolian, tectonic and fluvial processes; they also show a few circular features that could be impact structures. These observations imply that substantial surface modification has occurred over Titan's history. We have not directly detected liquids on the surface to date. Convective clouds are found to be common near the south pole, and the motion of mid-latitude clouds consistently indicates eastward winds, from which we infer that the troposphere is rotating faster than the surface. A detached haze at an altitude of 500 km is 150200 km higher than that observed by Voyager, and more tenuous haze layers are also resolved.